2021
DOI: 10.3390/ijms22157834
|View full text |Cite
|
Sign up to set email alerts
|

Individual DNA Methylation Pattern Shifts in Nanoparticles-Exposed Workers Analyzed in Four Consecutive Years

Abstract: A DNA methylation pattern represents an original plan of the function settings of individual cells and tissues. The basic strategies of its development and changes during the human lifetime are known, but the details related to its modification over the years on an individual basis have not yet been studied. Moreover, current evidence shows that environmental exposure could generate changes in DNA methylation settings and, subsequently, the function of genes. In this study, we analyzed the effect of chronic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…They reported hypomethylation at 341 CpG sites and hypermethylation of 364, with leading hits mapping to genes involved in pathways such as immune function and xenobiotic detoxification. More recently, in 2021 Rossnerova et al ( 91 ) reported their findings from a longitudinal study where they analyzed DNA methylation in leukocytes from 10 participants occupationally exposed to nanoparticles and 4 non-exposed controls over the course of 4 years. While they observed methylation changes within both groups, these were more pronounced in the exposed subjects, which they hypothesized to be part of adaptation to chronic nanoparticle exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported hypomethylation at 341 CpG sites and hypermethylation of 364, with leading hits mapping to genes involved in pathways such as immune function and xenobiotic detoxification. More recently, in 2021 Rossnerova et al ( 91 ) reported their findings from a longitudinal study where they analyzed DNA methylation in leukocytes from 10 participants occupationally exposed to nanoparticles and 4 non-exposed controls over the course of 4 years. While they observed methylation changes within both groups, these were more pronounced in the exposed subjects, which they hypothesized to be part of adaptation to chronic nanoparticle exposure.…”
Section: Resultsmentioning
confidence: 99%
“…During this time their exposure levels decreased, and subsequently they reported that LINE-1 methylation levels increased in 2013 compared to 2009 while hMLH1 methylation levels decreased. On the other hand, Rossnerova et al ( 91 ) reported what they call a “higher stability” in five differentially methylated CpG sites evaluated four times annually in 10 workers exposed to nanoparticles, suggesting an enforcement of epigenetic changes through continuous exposure. As these results suggest dynamic changes in DNA methylation in response to exposure levels, which are therefore likely to fluctuate over the lifecourse, they raise some important questions: how transitory are the observed global hypomethylation and gene-specific hypermethylation within exposed individuals?…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the discrepancies between the groups may be related to low sample numbers in CB. On the other hand, the differences in cell proportion can also be an important regulatory mechanism in response to the environment [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of studies demonstrating the epigenetic alterations resulting from nanomaterial exposure still lacks a connection with potential health risks. This is due to the unavailability of epigenetic modifications in epidemiological studies, except for only a few related to workplace nanomaterial exposure [ 123 , 132 , 141 , 142 , 143 ]. Like nanogenotoxicity, the assessment of the epigenetic toxicity of nanomaterials is mostly based on in vitro followed by in vivo (mice or rats) models ( Figure 6 ).…”
Section: Genotoxicity and Epigeneticsmentioning
confidence: 99%